2005
DOI: 10.1080/13880200490902455
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Ethnobotany:In Vitro. Antiplasmodial Activity of Seven Plants Identified in the Nigerian Middle Belt

Abstract: Seven methanol extracts of seven plants from seven plant families were screened for antimalarial properties. The plants were identified and selected from Gboko and Kastina-Ala local government areas in the Tivland ethnobotany in the Middle Belt Zone of Nigeria. Methanol plant extracts were evaluated for in vitro antimalarial properties using the lactate dehydrogenase technique, with a multiresistant strain of Plasmodium falciparum K1. Quantification of activity was by estimation of the concentration of extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 22 publications
(19 reference statements)
0
28
1
Order By: Relevance
“…Nauclea latifolia (NL) leaves were cited at 50% frequently by traditional healers as possessing antiplasmodial activity (Igwe et al, 2012). Nauclea latifolia SM (Rubiaceae) extract exhibited the least activity in the assay with an IC 50 value of 478.9 mg/ml compared to Chloroquine (Ajaiyeoba et al, 2004), and has been reported to inhibit the erythrocytic cycle of Plasmodium falciparum (Akubue and Mittal, 1982).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Nauclea latifolia (NL) leaves were cited at 50% frequently by traditional healers as possessing antiplasmodial activity (Igwe et al, 2012). Nauclea latifolia SM (Rubiaceae) extract exhibited the least activity in the assay with an IC 50 value of 478.9 mg/ml compared to Chloroquine (Ajaiyeoba et al, 2004), and has been reported to inhibit the erythrocytic cycle of Plasmodium falciparum (Akubue and Mittal, 1982).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Previous studies have demonstrated antibacterial [8,9], antimalarial [10] and antidiarrhoeic activity [11] for B. micrantha. Additionally, B. micrantha has been reported to inhibit -lactamase activity [12], RNA-dependent-DNA polymerase and ribonuclease H activities of human immunodeficiency type 1 reverse transcriptase (HIV-1 RT) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Some ethnic tribes in Akwa Ibom State, Nigeria, drink the leaf decoction of Nauclea latifolia (NL) for the prevention and cure of malaria (Udobre et al, 2013). N. latifolia have been reported to possess antiplasmodial activity (Ajaiyeoba et al, 2004;Asase et al, 2005;Adzu et al, 2013). Still little research data exist on the neurotoxicity of these antimalarial bio-chemicals in vivo studies especially their prophylactic impact.…”
Section: Introductionmentioning
confidence: 99%